Explore consumer needs and design purposes of smart clothing from designers' perspectives. Issue 3 (2nd September 2017) - Perry, Anna; Malinin, Laura; Sanders, Eulanda; Li, Yan; Leigh, Katharine
ABSTRACT: From both users' and creators' perspectives, this study examined: (1) designer-users' needs of smart clothing, (2) designer-identified consumer needs, (3) design purposes, and (4) the relationships among needs and design purposes. Fifteen participants were interviewed. Results indicated, first, users were most interested in affordable, fashionable, and enjoyable smart clothing. Second, designers believed the most important consumer needs were function, no technical problems, and affordability. Third, design purposes focused on function and solving technical problems. Fourth, two gaps existed: designers did not fully understand all consumer needs; although designers understood some needs, their design purposes did not always meet these needs. By investigating consumer needs from users who had purchasing experiences, this study provides a unique contribution to the scholarly literature. Findings identified gaps among user needs, designer-identified consumer needs, and design purposes, which will help industry and academia to develop more useful smart clothing.